Unlawful Acts In The Criminal Offense Of Document Forgery - Gatot Efrianto; Sabela Gayo; Abraham Quadan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The Unitary State of Indonesia consists of diverse ethnic groups and customary laws, governed under a sovereign legal framework to ensure the proper enforcement of regulations. As stipulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD 1945), “The State of Indonesia is a state based on law,” emphasizing that every individual who commits a criminal act must be held accountable according to applicable laws. However, various legal challenges continue to arise, especially amid rapid modernization and technological advancement, leading to new forms of criminal acts previously unknown, such as document forgery involving authentic deeds. An authentic deed is an official document prepared by or before a competent public official, serving as strong and binding evidence in legal proceedings as stated in Article 1870 of the Indonesian Civil Code (KUHPerdata). Given its probative value, authentic deeds hold a crucial role in legal certainty and public trust. Nevertheless, the increasing occurrence of forgery cases undermines the credibility of these documents and challenges the integrity of Indonesia’s legal system. Therefore, this study aims to analyze the legal implications and accountability mechanisms for the forgery of authentic deeds, emphasizing the need for stronger preventive regulations, stricter law enforcement, and enhanced oversight to uphold justice and protect the authenticity of legal instruments in Indonesia.